2019
DOI: 10.21608/ejfsat.2019.7078.1045
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ascorbic Acid and N-Acetyl Cysteine in Aspartame Induced Nephrotoxicity in Albino Rats

Abstract: Background: Aspartame is an artificial sweetener its consumption may cause some adverse health effects like metabolic syndrome, cancer and nephro-toxicity through oxidative stress of its metabolite. N acetyl cysteine (NAC) reduces kidney inflammation and improves renal function by improving microcirculation. Vitamin C is one of the most important antioxidant agents Aim of the study: to evaluate the protective effect of vitamin C and NAC in renal toxicity of aspartame either individually or in combination in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…These results could provide evidence on the therapeutic abilities of the transplanted BM-MSCs on AP most likely through their immune-modulatory effects, by reduction of T-cell infiltration and increased recruitment of regulatory T-cells. Moreover, the antioxidant therapeutic activity of vitamin C and NAC was demonstrated in experimentally induced tissue damage in albino rats [60]. As demonstrated in the present study, the adjuvant therapeutic value of AA and NAC antioxidants to BM-MSCs was confirmed by detection of significant higher body weight, lower blood glucose levels, and lower NF-κβ expression levels in combined therapy-treated group (group IV) compared with the BM-MSCs-treated group (group III).…”
Section: Discussionsupporting
confidence: 78%
“…These results could provide evidence on the therapeutic abilities of the transplanted BM-MSCs on AP most likely through their immune-modulatory effects, by reduction of T-cell infiltration and increased recruitment of regulatory T-cells. Moreover, the antioxidant therapeutic activity of vitamin C and NAC was demonstrated in experimentally induced tissue damage in albino rats [60]. As demonstrated in the present study, the adjuvant therapeutic value of AA and NAC antioxidants to BM-MSCs was confirmed by detection of significant higher body weight, lower blood glucose levels, and lower NF-κβ expression levels in combined therapy-treated group (group IV) compared with the BM-MSCs-treated group (group III).…”
Section: Discussionsupporting
confidence: 78%